Case report: Bullous pemphigoid combined with Sjögren’s syndrome complicated by central nervous system infection - Chen, Xing-Yue; Chen, Jun; Long, Kun-Lan; Ding, Peng; Li, Rong; Zhi, Li-Jia (Frontiers in Immunology, 2024)
Background Bullous pemphigoid (BP) is the most common autoimmune blistering skin disease in humans, characterized by tense blisters, erosions, urticarial lesions, and itching on normal or erythematous skin. Many autoimmune diseases are considered comorbidities of BP, but clinical case reports of BP complicated by Sjögren’s syndrome are very scarce. Furthermore, cases of central nervous system infection secondary to both autoimmune diseases are even rarer. Case presentation We report a 74-year-old woman diagnosed with bullous pemphigoid, who showed relief of active lesions after treatment with methylprednisolone and dupilumab injections. However, she was admitted for pulmonary infection during which she was diagnosed with Sjögren’s syndrome (SS). Subsequently, the patient developed altered consciousness, indicating a central nervous system infection. Adjustment of steroid dosage and aggressive antimicrobial therapy led to alleviation of symptoms. Conclusion The coexistence of autoimmune subepidermal blistering diseases and SS is rare. The role of SS in the pathogenesis of skin lesions is unclear, and the relationship between these blistering diseases and SS remains elusive. Further research is needed to determine whether there are common pathological mechanisms between the two conditions.